Personal finance 101 : from saving and investing to taxes and loans, an essential primer on personal finance - Mill, Alfred (Adams 101, 2020)
"Managing your finances can be overwhelming at times. But it doesn't have to be! Personal Finance 101 will provide you with all the skills you need to make good financial decisions and grow your personal wealth. Full of must-have advice and organized in an easy-to-read format, this book provides a wealth of knowledge on personal finance basics including: -Choosing your bank (and why it matters) -Building an emergency fund -Salary and benefit packages -Where your money is going (and how to keep more of it) -Refinancing or consolidating student loans -Health and property insurance -Building credit responsibly -How to get a mortgage Use this guide and make the most of the money you have, plan for future purchases like a house or a vacation, save for retirement, or simply become more financially responsible. Perfect for finance beginners or those looking to refresh their knowledge, Personal Finance 101 is the one-stop shop for all of your personal finance questions!"--